Analysis of spatial homogeneity of integrity standards in selected eu oecd countries - Beata Zofia Filipiak; Marek Dylewski; Katarzyna Cheba (e-Finanse: Financial Internet Quarterly, 2018)
The principle of transparency not only is changing but its importance is increasing. International organizations, including the OECD, are seeking to develop harmonized standards of transparency in public administration. This fact is of particular importance in the search for common solutions for the OECD countries in the implementation of transparency standards, but also this organisation has sought adequate methods for measuring implementation of these standards. The main purpose of the study is to analyze the level of spatial homogeneity in the area of application of the standards of 'integrity' of the OECD, which are an expression of the principle of transparency in the member states of this organization, on the European continent. In the study vector calculus was used.
Keywords: H39; H87; C61; 330; public finances; the principle of transparency; "integrity"; spatial homogeneity